Sporotrichosis caused by Sporotrix globosa in an elderly male farmer at the site of a cat scratch - Yuka Sakai; Yuta Norimatsu; Taro Akatsuka; Toshihisa Hamada; Harumi Gomi; Makoto Sugaya (Medical Mycology Case Reports)
We report a case of sporotrichosis in an elderly male farmer at the site of a cat scratch scar.An 84-year-old Japanese farmer was scratched by his cat two months before his visit to our hospital.A skin biopsy was performed. Tissue culture revealed the presence of Sporothrix globosa.The patient was treated with oral itraconazole 200 mg/day for 13 months due to a slow healing ulceration, and the symptoms resolved. (71 words).